Information-technological systems of the competitive wholesale electricity market in Ukraine - Kyrylenko O.V.; Blinov I.V.; Khorhmazov G.S.; Popovych V.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
Maintenance of work and administration of the bilateral contracts electricity market and the balancing market (BCBM) in Ukraine demands working out and introduction of information-technological systems and a corresponding communication systems of the system operator, the market operator and the market finance administrator. The basic condition of successful functioning of BCBM is clear distribution of roles and maintenance of interactions between these information-technological.The basic functions and the organisation of interactions of information-technological and administration system of BCBM are defined. The information-technological system of BCBM includes: information-technological system of System operator, Market operator and market finance administrator.Basic elements are defined and ways of the organization of interactions between them in aria of information-technology systems which provide performance of functions of BCBM work in Ukraine are established. The structure of these systems is specified.